The critics on the history of Arabic grammar - Yaacob, Solehah@Nik Najah Fadilah (International Institute of Islamic Civilisation and Malay World (ISTAC), International Islamic University Malaysia (IIUM), 2018)
This study aims to critically examine IgnazGolziher’s allegations on the beginnings of Arabic linguistics. According to him, the Arabic short vowel symbols did not originate in the Arab world but were adopted from the Levant. The same he assumed in regard to the three different parts of speech, namely name (ism), verb (fiÑil), and particle (harf), which allegedly presupposed the knowledge of Aristotle’s De Interpretations falsely attributed to ÑAli (Karramallahuwajhah) . Goldziher explained this connection with the scholastic disputes occurring between the different theological schools in the first century AH, with special reference to the dogmatic differences between the Murji´ah and the Qadariyyah sects. Theological debates on various doctrines were held at the same time by Eastern Christians based on the teachings of John of Damascus. In the eyes of Goldziher, these debates – based on the assumption that since they occurred in the same century – they had to be related, and furthermore, St. John of Damascus must have borrowed his ideas from Aristotle. Since no Arabic sources speak of this connection, he raises his own suspicions, namely that Muslim sources refused to admit the borrowing of ideas from the Christians. This study serves the purpose of investigating his allegations in regard to the origin of Arabic grammar and syntax and of deciding the extent of his scholarly bias. The researcher adopts a theoretical and analytical approach based on linguistic studies. In order to arrive at a balanced judgment with regard to this conflict, the linguistic corpus, as well as the historical background of transmission is being analyzed.